Studi Komparasi Metode Pengomposan Secara Windrow, Bata Berongga Dan Vermikomposting - Nailul Afifah; Shinfi Wazna Auvaria; Sulistiya Nengse; Teguh Taruna Utama; Yusrianti Yusrianti (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2022)
Composting is a method of processing organic waste using the help of microorganisms to produce compost products. Compost quality must comply with SNI 19-7030-2004 so that it is safe to use for soil. The composting process can occur aerobically or anaerobically. Aerobic composting is composting with the help of aerobic microorganisms in sufficient oxygen conditions. While anaerobic composting is composting using the help of anaerobic microorganisms in conditions without oxygen. Windrow composting, brick bin composting, and vermicomposting are types of aerobic composting that are suitable for MRF (TPST) scale. Comparison test was conducted to determine the best composting method for TPST Banjarbendo. The comparisons made include parameters of pH, temperature, C-organic, N-total, C/N ratio, and the percentage of organic waste reduction. The composting method was chosen based on the results of the tests carried out on the compost product from the three composting methods.The best composting method is hollow brick composting which has a temperature of 27°C, C-organic 10.21, N-total 0.87, C/N ratio 11.74, and percentage reduction is 65,2%.